Assessment of ranges of rest postures of human lower limbs. - Naddeo, A.; Cappetti, N.; Vallone, M. (Work, 2019)
BACKGROUND: Several comfort perception models have proposed an objective method to evaluate "effects in the internal body" and "perceived comfort". Postural comfort is one aspect of comfort/discomfort perception, and this current work adds to existing knowledge toward a more objectified posture evaluation for comfort. OBJECTIVE: The authors have used the concept of Range of Rest Posture (RRP), as proposed by Apostolico et al. The study focused on the identification of RRP within the Comfort Range of Motion (CROM) for lower limbs. METHODS: The proposed method is based on extensive experimental work involving 114 healthy individuals (59 males and 55 females) ranging from 20 to 40 years old. The age range was narrowed to avoid an age-clustering of results due to inhomogeneity of the statistical sample. Data were processed using statistical methods for identifying the RRP in the experimental CROM. Several Maximum Level of Comfort (MLC) positions were found within the RRP. RESULTS: RRPs for lower limbs of men and women have been identified and can be used for virtual comfort assessment. CONCLUSIONS: This paper shows a method to evaluate in a more objective way the subjective postural comfort perception and results allow researchers to improve models for the virtual preventive comfort assessment.